Chile, Democracy is Over: Institutional Crisis in the Chilean 18-O - Ramírez, Carlos; Y´añez-Urbina, Cristopher; Salinas, Iván (Re-presentaciones: Periodismo, comunicación y sociedad, 2020)
The article analyzes the events that occurred between October 4th and November 22nd, 2019 in Chile, with the proposal both to grant a political panorama located in the national context and to be able to abstract that existing function between a nineteenth-century policy based in representative democracy and a social conformation that constantly escapes its schemes. In this way, both the archaeological ground is approached from where the rationality of representative democracy stands. What is subsequently contrasted with the two main strategies deployable by modern institutions to manage the conflict. It concludes the existence of a deep crisis of representative democracy and nineteenth-century mechanisms that is evident in an act that borders fascism.